Towards the Non-Mertonian Ethos of a Non-Mertonian Science: Situating the Research Value of Openness - Nordmann, Alfred (NOvation — Critical Studies of Innovation, 2024)
It is hard to disagree with the thrust of René von Schomberg’s position paper. It is driven by the worry that current conceptions of “open science” are all too impoverished – that they need to be complemented by the social practice of “mutual responsiveness”. In terms of political theory or notions of democracy, on the one hand, in terms of socially relevant research practice, on the other hand, only an ambitious commitment to open science will be robust enough to make a difference and contribute to the solution of pressing problems. In contrast, it is paying lip service only to the ideal of openness when “open science” becomes reduced to “open access publishing” or data storage rituals. As von Schomberg shows, this might actually deepen disparities and redundancies within dysfunctional science.